The electromechanical study on Magnesium sacrificial anode in cathodic protection - Mohd Nazree Derman; Zulkifli Zainon; Shaiful Rizam Shamsudin (Universiti Kebangsaan Malaysia (UKM), 2009)
anized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.